2007
DOI: 10.1523/jneurosci.2382-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Regulates Bcl-w and Bim Expression: Role in Protection against β-Amyloid Peptide-Induced Neuronal Death

Abstract: Estrogen is neuroprotective against a variety of insults, including ␤-amyloid peptide (A␤); however, the underlying mechanism(s) is not fully understood. Here, we report that 17␤-estradiol (E2) selectively regulates neuronal expression of the Bcl-2 family (bcl-2, bcl-x, bcl-w, bax, bak, bad, bik, bnip3, bid, and bim).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(90 citation statements)
references
References 84 publications
(93 reference statements)
3
84
0
3
Order By: Relevance
“…In addition, bFGF, but not NGF decreased Ca++ disturbances in hippocampal neurons [26]. Estrogen alters expression of Bcl proteins involved in apoptosis pathways [41].…”
Section: Discussionmentioning
confidence: 93%
“…In addition, bFGF, but not NGF decreased Ca++ disturbances in hippocampal neurons [26]. Estrogen alters expression of Bcl proteins involved in apoptosis pathways [41].…”
Section: Discussionmentioning
confidence: 93%
“…Among the BH3-only proteins, Bim plays a critical role in a variety of neuronal death paradigms, including cerebellar granule neurons (CGNs) deprived of activity (Putcha et al, 2001;Shi et al, 2005), sympathetic neurons during removal of nerve growth factor (NGF) (Whitfield et al, 2001), and cortical neurons exposed to ␤-amyloid peptide (Biswas et al, 2007b;Yao et al, 2007). For example, CGNs and sympathetic neurons from Bim knock-out mice display a significant delay in apoptosis (Putcha et al, 2001;Coultas et al, 2007), demonstrating that Bim is a critical mediator of a proapoptotic signaling pathway in these neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the present study demonstrated that OVX for 5 weeks increased neuronal ABAD level in the mouse hippocampus. Taken together with recent studies showing that estrogen protects neuronal cells from Aβ-induced apoptosis by regulating the expression of mitochondrial proteins (Yao et al, 2007;Nilsen et al, 2006), it is suggested that estrogen also directly regulates ABAD expression and that the cessation of negative regulation by OVX results in the overexpression of ABAD. On the other hand, it is also demonstrated that ABAD expression is increased in an Aβ-rich environment (Yan et al, 1997;He et al, 2002).…”
Section: Discussionmentioning
confidence: 71%
“…In vitro findings from cultured neurons suggest that estrogen may prevent AD pathogenesis by reducing Aβ generation, protecting against Aβ-mediated neurotoxicity, and enhancing Aβ clearance (Xu et al, 2006;Li et al, 2000). In addition, recent studies indicate that estrogen protects against Aβ-induced neuronal death by maintaining mitochondrial function (Yao et al, 2007;Nilsen et al, 2006). These finding indicate that Aβ and estrogen relate closely and incompatibly regulate Aβ-mediated AD pathology.…”
Section: Introductionmentioning
confidence: 99%